Human Muse cells isolated from preterm- and term-umbilical cord delivered therapeutic effects in rat bleomycin-induced lung injury model without immunosuppressant - Kaung Htet Nay Win; Yoshihiro Kushida; Keiji Yamana; Sota Iwatani; Makiko Yoshida; Nanako Nino; Cho Yee Mon; Hiroyuki Ohsaki; Shingo Kamoshida; Kazumichi Fujioka; Mari Dezawa; Noriyuki Nishimura (Stem Cell Research & Therapy, 2024)
Abstract Background Bleomycin (BLM)-induced lung injury is characterized by mixed histopathologic changes with inflammation and fibrosis, such as observed in human patients with bronchopulmonary dysplasia, idiopathic pulmonary fibrosis, and chronic obstructive pulmonary disease. Although no curative therapies for these lung diseases exist, stem cell therapy has emerged as a potential therapeutic option. Multilineage-differentiating stress-enduring (Muse) cells are endogenous pluripotent- and macrophage-like stem cells distributed in various adult and fetal tissues as stage-specific embryonic antigen-3-positive cells. They selectively home to damaged tissue by sensing sphingosine-1-phosphate and replace the damaged/apoptotic cells by in vivo differentiation. Clinical trials for some human diseases suggest the safety and therapeutic efficacy of intravenously injected human leukocyte antigen-mismatched allogenic Muse cells from adult bone marrow (BM) without immunosuppressant. Here, we evaluated the therapeutic effects of human Muse cells from preterm and term umbilical cord (UC), and adult BM in a rat BLM-induced lung injury model. Methods Rats were endotracheally administered BLM to induce lung injury on day 0. On day 3, human preterm UC-Muse, term UC-Muse, or adult BM-Muse cells were administered intravenously without immunosuppressants, and rats were subjected to histopathologic analysis on day 21. Body weight, serum surfactant protein D (SP-D) levels, and oxygen saturation (SpO2) were monitored. Histopathologic lung injury scoring by the Ashcroft and modified American Thoracic Society document scales, quantitative characterization of engrafted Muse cells, RNA sequencing analysis, and in vitro migration assay of infused Muse cells were performed. Results Rats administered preterm- and term-UC-Muse cells exhibited a significantly better recovery based on weight loss, serum SP-D levels, SpO2, and histopathologic lung injury scores, and a significantly higher rate of both Muse cell homing to the lung and alveolar marker expression (podoplanin and prosurfactant protein-C) than rats administered BM-Muse cells. Rats receiving preterm-UC-Muse cells showed statistically superior results to those receiving term-UC-Muse cells in many of the measures. These findings are thought to be due to higher expression of genes related to cell migration, lung differentiation, and cell adhesion. Conclusion Preterm UC-Muse cells deliver more efficient therapeutic effects than term UC- and BM-Muse cells for treating BLM-induced lung injury in a rat model.